Anatomy of the pedicled anterolateral thigh flap for phalloplasty in transitioning‐males. Issue 2 (27th December 2017) - Terrell, Mark; Roberts, Wallisa; Price, Charles Wesley; Slater, Michael; Loukas, Marios; Schober, Justine
Abstract : Incidence of transexualism and request for neophalloplasty is increasing yielding a current prevalence of trans‐male in the USA of 1:2500. Surgeons have explored various techniques to improve desirable outcomes of neophallic construction, decrease the length of surgery, and minimize stigmatizing scars. The anterolateral thigh (ALT) flap is an alternative to the traditional radial forearm flap for patients who do not want a forearm scar. Surgical text descriptions were enhanced by the creation of new anatomic illustrations. Anatomy of the donor and recipient sites as well as the surgical technique leading to creation of the neophallus are demonstrated in detail with new relevant illustrations. The ALT flap is a skin, fat and fascia flap that is usually supplied by the descending branch of the lateral circumflex femoral vessels and the lateral femoral cutaneous nerve. However, variability in neurovascular supply does exist with important clinical implications. In the pedicled surgical procedure, neurovascular supply is left partly attached to the donor site ("pedicle") and simply transposed to the perineum, keeping the pedicle intact as a conduit to supply the tissue with blood and innervation. ALT flap offers clinical advantages of less obvious donor site concealable with clothing, decreased surgical time, preservation of erogenous sensation and vascular supply of the flap without microsurgical anastomosis of nerves and vessels, and good potential for urethroplasty. This surgery may be difficult in patients with thicker skin and more subcutaneous thigh fat. Clin. Anat, 2017. © 2017 Wiley Periodicals, Inc. © 2017 Wiley Periodicals, Inc.